STATE-BUILDING PROCESS IN UZBEKISTAN: MANY MILES TO GO - Gürhan Ünal (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Thisstudy examines the developments in post-Soviet Uzbekistan in the field of statebuilding. With the dissolution of USSR, newly independent states struggled tofunction as independent nation-states since the transition efforts fromCommunism to post-Communism created an uncharted area for the post-Sovietsocieties. Transition studies gained widespread attention with thedemocratization of Latin America and Southern Europe. However, it becameevident that current transition literature which solely focuses ondemocratization and marketization lacks the explanatory power on transitionprocess of post-Soviet states due to the Soviet legacy which left its marks notonly in terms of democracy and economy but also on national-identity andreligious affairs. Therefore, it is argued that a quadruple transition modelwhich focuses on democratization, marketization, stateness and nationality ismore appropriate to analyze the developments in post-Soviet states. InUzbekistan, transition process was operated by Islam Karimov until 2016.Contrary to some other Central Asian countries, Uzbekistan enjoyed a morestable transition process mostly due to Karimov’s authoritarian rule. However,after more than two decades, it is difficult to consider Uzbekistan neither asa full democracy nor as a market economy. Moreover, the struggle betweenso-called radical Islamist groups and the government poses serious threats tothe stability of the country. Lately Shavkat Mirziyoyev’s presidency following thedeath of Karimov created a more fertile ground for further democratization ofUzbekistan. Considering these developments, this study evaluates state-buildingpolicies of Uzbekistan in five topics regarding nation-building,democratization, marketization, religion and foreign affairs. It is argued thatdespite relative stability and progress, Uzbekistan is far from being anexample of successful transition.